Performance Evaluation of Dolomite Fertilizer Production: AHP and Scoring System Approach Based on Performance Prism - Sholeha, Fitriatus; Pulansari, Farida (Rekayasa, 2024)
Fertilizer production often faces various performance issues that can affect efficiency and productivity. One of the main problems is the instability in the quality of raw materials, which can result in variations in the quality of the final product. Workforce performance is also a critical factor, where inadequate training and low motivation can reduce productivity. The lack of an appropriate performance measurement system, such as relevant and accurate Key Performance Indicators (KPIs), can make it difficult for companies to monitor and improve their overall performance. To address these challenges, a performance measurement system is needed that can integrate various aspects of the company (stakeholders). This performance measurement system must be able to accommodate the interests of various parties involved in the company's operations to produce more accurate and relevant information. The performance measurement approach referred to is known as the Performance Prism. It is then supported by using the Objective Matrix (OMAX) method to determine the ranking and class calculation of each KPI and the Traffic Light System (TLS). Based on performance measurements using the Performance Prism, Analytic Hierarchy Process (AHP), and Scoring System at PT. XYZ, there are 53 KPIs divided among various stakeholders. From this analysis, it can be concluded that the design of the company's performance measurement encompasses various aspects involving both internal and external stakeholders. The total performance index of 13.43 indicates overall good performance. In this case, the total KPIs used are 53 KPIs, which include 10 KPIs for employee stakeholders, 5 KPIs for owner stakeholders, 10 KPIs for customer stakeholders, 5 KPIs for government stakeholders, 4 KPIs for investor stakeholders, 10 KPIs for supplier stakeholders, 4 KPIs for partner stakeholders, and 5 KPIs for surrounding community stakeholders. According to the results of the Objective Matrix (OMAX) and Traffic Light System (TLS), it can be seen that 47 KPIs fall into the green category, indicating good achievement, while 3 KPIs fall into the yellow category, and 3 other KPIs fall into the red category, indicating areas requiring further attention for improvement.